The Influence of Game Use and Video Game Content in Managing Students' Emotional Balance Amid Academic Pressure - Khairunnisa, Erinna; Nurhidayatulloh, Ade (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
The rapid development of digital technology has made games and video game content an integral part of students' lives today. Amidst high academic pressure, students often experience stress and difficulty in maintaining emotional balance. This study aims to analyze the effect of using games and video game content in managing students' emotional balance amid academic pressure. The method used is a descriptive quantitative approach with purposive sampling technique and data collection through online questionnaires to college students who have experience playing games and watching video game content. The results showed that most college students allocated more than 3 hours a day to play games, which helped them manage stress and maintain emotional balance. Casual games were most effective in reducing stress and improving mood. However, excessive use can interfere with academic concentration, so time management is necessary. In addition, games provide a space to express emotions and interact socially, which contributes to students' emotional balance. Overall, games can be an effective tool in the management of emotional balance if utilized carefully.